Combined early palliative care for non-small-cell lung cancer patients: a randomized controlled trial in Chongqing, China - Chen, Mengting; Yu, Huiqing; Yang, Liejun; Yang, Hong; Cao, Haoyang; Lei, Lei; Ma, Liling; Liu, Shihong; Tian, Ling; Wang, Sixiong (Frontiers in Oncology, 2023)
Purpose More effective approaches are needed to improve the prognosis of non-small-cell lung cancer (NSCLC) patients. Thus, we used the E-warm model to assess how early integration of interdisciplinary palliative care was related to the quality of life (QoL), psychological functioning, pain management, and nutrition factors of NSCLC patients. Methods This randomized controlled trial enrolled 280 newly diagnosed NSCLC patients, which were randomly divided (1:1) into combined early palliative care (CEPC) and standard oncological care (SC) groups. At baseline and after 24 weeks, the Functional Assessment of Cancer Therapy-Lung (FACT-L) scale, Hospital Anxiety and Depression Scale (HADS), and the Patient Health Questionnaire-9 (PHQ-9) were used to assess QoL and psychological function, respectively. The Numerical Rating Scale (NRS) and Patient-Generated Subjective Global Assessment (PG-SGA) were used to assess cancer patients’ pain and nutrition levels. The primary outcome was overall survival (OS). Secondary outcomes comprised changes in the QoL, psychological functioning, pain, and nutrition state. The intention-to-treat method was applied for analysis. This study was registered at www.chictr.org.cn (ChiCTR2200062617). Results Of the 140 patients enrolled in the CEPC and SC groups, 102 and 82 completed the research. The CEPC group presented higher QoL than the SC group (p < 0.05). Additionally, fewer patients presented depressive symptoms in the CEPC group than in the SC group (p < 0.05), as well as better nutritional status (p = 0.007) and pain management (p = 0.003). Compared to the SC group, CEPC patients had significantly longer OS (20.4 vs. 24.6 months, p = 0.042; HR: 0.19; 95% CI: 0.04-0.85, p = 0.029). Conclusion With combined early palliative care, NSCLC patients lived longer, had better QoL, were psychologically stable, were in less pain, and were more nutritionally satisfied.